Supplements to the Proceedings on Applied Botany, Genetics and Breeding: dedicated to the 115th anniversary of the journal - article Editorial (Труды по прикладной ботанике, генетике и селекции, 2024)
Proceedings on Applied Botany, Genetics and Breeding is the oldest specialized journal in Russia. It has been published in St. Petersburg with supplements since the early 20th century up to the present day. In 2023, the journal celebrated its 115th anniversary. The journal Bulletin of Applied Botany was founded in 1908 by Robert Regel, Head of the Bureau of Applied Botany, the Russian botanist who laid the foundations of applied botany in Russia. The journal rightfully occupied a leading place among Russian scientific periodicals and acquired the core authority in applied botany and breeding within Russia. During the interwar period of Soviet Russia and the USSR (1917–1940), the journal was headed by the world-famous Russian scientist Academician Nikolay Vavilov, a public figure and official, a recognized expert in the field of plant genetics, breeding, cultivation, and immunology.Since 1908, publicly available original or translated articles recounting the current (at the time of publication) state of knowledge in various sectors of applied botany and plant breeding have been published in the form of supplements to the Proceedings.Supplements were published from 1908 through 1937. The only exception in the postwar Soviet period was the publication of the collection of guidelines entitled Methods for the Comprehensive Study of Photosynthesis in 1969, formatted as a special supplement to volume 40. Fundamental publications by Russian and foreign authors were noticed by domestic readers much faster when they appeared as supplements to a well-known journal that contained original articles, research results on individual crops, summaries and reviews in the field of applied botany, plant breeding and genetics.Academician Nikolay Vavilov, who headed the editorial committee, impelled all of his staff members, without exception, to publish their research findings first in the Proceedings, and only after that in other editions.Supplements 1–21 were published under the editorship of Robert Regel, and beginning from supplement 22 under the editorship of Nikolay Vavilov. Following the consecutive numbering on the supplements, 84 supplements should have been published, plus an additional one to volume 40, but de facto not all of the announced supplements appeared in print.The mission undertaken by the Editorial Board of the Proceedings on Applied Botany, Genetics and Breeding for the journal’s 115th anniversary was to present a complete list of supplements to the journal in order to familiarize the scientific community and other readers with the books published as supplements in 1908–1937. It is seen as a good opportunity to trace how the prioritized research topics in the fields of botany, plant breeding and genetics changed over a century and to encourage readers to get acquainted with the primary sources, browsing through the old pages of VIR’s journal.The list was compiled by the staff members of VIR’s Library and Publishing Department: Irina V. Kotelkina, Elena A. Sokolova (Dr. of Biol. Sci.), and Anton G. Krylov.